Intracranial Capillary Hemangioma in the Posterior Fossa of an Adult Male - Jordan Nepute; Jinping Lai; Yihua Zhou (Case Reports in Radiology)
Intracranial capillary hemangioma (ICH) is a rare entity, with approximately 24 reported cases in the literature. There are only three reported cases of ICH in an adult male. In this case report, we describe the fourth documented case of ICH in an adult male and, to the best of our knowledge, the first ever documented case of ICH in the posterior fossa of an adult male. We also discuss its imaging appearance and differential diagnosis.